A crisis management approach to mission survivability in computational multi-agent systems - Byrski, Aleksander; Kisiel-Dorohinicki, Marek; Carvalho, Marco (Wydawnictwa AGH, 2010)
In this paper we present a biologically-inspired approach for mission survivability (considered as the capability of fulfilling a task such as computation) that allows the system to be aware of the possible threats or crises that may arise. This approach uses the notion of resources used by living organisms to control their populations. We present the concept of energetic selection in agent-based evolutionary systems as well as the means to manipulate the configuration of the computation according to the crises or user's specific demands.

W artykule prezentujemy biologicznie inspirowany mechanizm wspomagający utrzymanie krytycznych zadań (tzw. mission survivability) który umożliwia wykrywanie oraz przeciwdziałanie wybranym zagrożeniom. Przedstawione podejście wzorowane jest na wykorzystywaniu przez żywe organizmy zasobów do kontroli populacji. Prezentujemy koncepcje selekcji energetycznej mającej zastosowanie w ewolucyjnych systemach wieloagentowych (EMAS) oraz sposoby konfiguracji obliczenia w celu przeciwdziałania sytuacjom kryzysowym, według preferencji użytkownika.
Utrzymanie krytycznych zadań oparte na zarządzaniu kryzysowym w obliczeniowych systemach wieloagentowych
Computer Science
Bibliogr. s. 112-113.
Keywords: agent systems; crisis management; systemy agentowe; zarządzanie kryzysowe; soft computing; soft computing